Взаємодія фаз системи “вода–газ” у гірських породах та формування покладів природного газу - Безручко, К. (Геологія і геохімія горючих копалин, 2010)
Розглянуто три стани насиченості рідиною порового простору гірських порід
залежно від відносних фазових проникностей води та газу, коли відносна фазова
проникність води дорівнює нулю, відносні фазові проникності води та газу рівні
між собою, відносна фазова проникність газу дорівнює нулю. На основі цього складено схему взаємовпливу та взаємодії окремих фаз у поровому просторі зцементованих псамітових порід (пісковиків). Систему “вода–газ” розглядаємо як термодинамічну, яка прагне до рівноваги. Вона може мати декілька рівноважних станів
(4 статичні та 2 динамічні). Найбільш стабільним є стан, за якого відносні фазові
проникності води та газу рівні між собою, а їхня сумарна проникність мінімальна.
Запропоновано формулу для розрахунку водонасиченості, яка відповідає рівноважному насиченню водою та газом. Відносну рівноважну фазову проникність також
визначають залишковою водонасиченістю. З її збільшенням, закономірно, за лінійною залежністю, точка рівноваги зміщується до області більшої водонасиченості та
меншої відносної фазової проникності. За великих значень природної вологості
(водонасиченість – понад 50 %) здатність пласта бути колектором визначають співвідношенням зв’язаної та вільної води. Three states of saturation of rocks pore space by liquid have been considered depending on relative phase permeabilities of water and gas. They are: relative phase water
permeability is equal to zero, relative phase water permeability and relative phase gas
permeability are equal between themselves, relative phase gas permeability is equal to 0.
On the basis of these conditions the scheme was drawn up of the influence and interaction
of separate phases in pore space of consolidated psammitic rocks (sandstones). The existence model of system “water–gas” in a rocks massif was offered. The system “water–gas”
is considered as thermodynamic system which aspires to the equilibrium. This system can
have a few equilibrium states (4 static and 2 dynamic). Most stable is a condition which
relative phase water permeability and relative phase gas permeability are equal at, and
their total permeability is minimum. Degree of saturation, at which this state comes, is
determined by a bounded water content (residual water saturation). Formula is proposed
for the calculation of water saturation at equilibrium saturation by water and gas. The
equilibrium water saturation calculation values coincide with empiric values of other researchers. Relative equilibrium phase permeabilities also were determined by residual
water saturation. With its increase, appropriately, on linear dependence, a point of equilibrium is displaced to the zone of greater water saturation and less relative phase permeabilities. From 55 % – for the rocks of not containing bounded water and by phase permeabilities
about 16 %, to 90 % at screening horizons with zero permeability. The condition of gas
deposit existence is a gas saturation 50 % and more under the conform pressure. At the
large values of natural humidity (water saturation more than 50 %), ability of geological
horizon to be a reservoir is determined by ratio of bounded and free water. A gas deposit
in a rock massif can be formed if the bounded water content (residual water saturation)
does not exceed 50 %.